Investigating metacognitive awareness of academic learning among students of English education program of IKIP PGRI Pontianak - Luthfiana, Annisa; Irwan, Dedi; Putra, Muhammad Iqbal Ripo; Masrokhin (Journal of English Language Proficiency, 2024)
This descriptive study examined metacognitive awareness levels among students in the English Education Study Program at IKIP PGRI Pontianak. Using a cross-sectional survey, data was collected from 420 students across various academic years and backgrounds. The Metacognitive Awareness Inventory (MAI) by Schraw & Dennison (1994), consisting of 52 items across eight indicators and two main factors, was used to assess students' metacognitive skills. Analysis with descriptive statistics revealed that 86% of the students reported a high level of metacognitive awareness. This is significant as metacognitive awareness is linked to academic success, such as higher-grade point averages. The most frequently reported indicators were Debugging Strategies, Conditional Knowledge, and Evaluation, while Information Management Strategies emerged as the least used. Notably, students scored lower on items related to remembering information and using visual aids like diagrams. These results highlight both strengths and areas for growth in students' metacognitive awareness, highlighting specific skills that could be further developed to enhance their academic performance.